2012
DOI: 10.1017/s1751731111001856
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between growth and reproductive traits in Nellore cattle

Abstract: The objective of this study was to evaluate the genetic relationship between postweaning weight gain (PWG), heifer pregnancy (HP), scrotal circumference (SC) at 18 months of age, stayability at 6 years of age (STAY) and finishing visual score at 18 months of age (PREC), and to determine the potential of these traits as selection criteria for the genetic improvement of growth and reproduction in Nellore cattle. The HP was defined as the observation that a heifer conceived and remained pregnant, which was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 28 publications
6
23
1
7
Order By: Relevance
“…Genetic correlations among the reproductive traits STAY, NC53 and HR were similar and superior compared with those estimated between SC and these traits. Genetic correlation between STAY and SC (0.12 ± 0.058) was similar to that reported by Santana et al (2012), 0.17. These authors suggested that there is no antagonism between SC and STAY; in other words, selection on one trait would produce little or no effect on other.…”
Section: Resultssupporting
confidence: 87%
“…Genetic correlations among the reproductive traits STAY, NC53 and HR were similar and superior compared with those estimated between SC and these traits. Genetic correlation between STAY and SC (0.12 ± 0.058) was similar to that reported by Santana et al (2012), 0.17. These authors suggested that there is no antagonism between SC and STAY; in other words, selection on one trait would produce little or no effect on other.…”
Section: Resultssupporting
confidence: 87%
“…For SC, mean heritability ranged from 0.15 to 0.23 across the environmental gradient. These estimates are lower than those reported by Vargas et al (1998), Eler et al (2004) and Santana et al (2012b), who found heritabilities ranging from 0.28 to 0.57 for SC of purebred animals. However, similar estimates were obtained by Santana et al (2010) in a study, with part of the present composite cattle raised in the Midwest and Southeast of Brazil.…”
Section: Resultscontrasting
confidence: 74%
“…For BW, the results obtained for the direct heritability coefficient (h 2 a ) were similar between the four models (Table 5), and similar results were presented by Santana et al (2012) and Regatieri et al (2012). The estimate for h 2 a to PWG, was the same as that reported by Tonussi et al (2015), showing a later response to direct selection.…”
Section: Traitssupporting
confidence: 78%